2016
DOI: 10.1177/000313481608201013
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Access and Outcomes of Cholecystectomy in the United States

Abstract: Disparities in access to health care between white and minority patients are well described. We aimed to analyze the trends and outcomes of cholecystectomy based on racial classification. The Nationwide Inpatient Sample database was reviewed for all patients undergoing cholecystectomy from 2009 to 2012. Patients were stratified as white or non-white. A total of 243,536 patients were analyzed: 159,901 white and 83,635 non-white. Non-white patients had significantly higher proportions of Medicaid (25% vs 9.3%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…cholecystectomies, but men tend to have more complex and longer procedures which may explain their less favorable outcomes. 28,29 In agreement with our findings, Carbonell et al found in a US-nationwide study in 2000 that male gender was linked to higher charges, longer LOS, and increased morbidity and mortality after cholecystectomy. 3 Black race was an independent predictor for increased LOS and total cost.…”
Section: Ijmssupporting
confidence: 92%
“…cholecystectomies, but men tend to have more complex and longer procedures which may explain their less favorable outcomes. 28,29 In agreement with our findings, Carbonell et al found in a US-nationwide study in 2000 that male gender was linked to higher charges, longer LOS, and increased morbidity and mortality after cholecystectomy. 3 Black race was an independent predictor for increased LOS and total cost.…”
Section: Ijmssupporting
confidence: 92%
“…However, these results may have been influenced by confounding if healthier patients were more likely to undergo an earlier operation. In addition, evidence from 243 536 patients in the US Nationwide Inpatient Sample database showed that non-White patients had higher rates of emergent admission compared with White patients (84% vs 78%, respectively; P < .001), suggesting there are disparities in health care access for non-White patients who have acute cholecystitis . In summary, early cholecystectomy was associated with significantly better outcomes than delayed cholecystectomy …”
Section: Treatmentmentioning
confidence: 96%
“…In addition, evidence from 243 536 patients in the US Nationwide Inpatient Sample database showed that non-White patients had higher rates of emergent admission compared with White patients (84% vs 78%, respectively; P < .001), suggesting there are disparities in health care access for non-White patients who have acute cholecystitis. 70 In summary, early cholecystectomy was associated with significantly better outcomes than delayed cholecystectomy. [66][67][68][69] Approximately 2% to 15% of patients undergoing laparoscopic cholecystectomy must be converted to open cholecystectomy.…”
Section: Early Vs Delayed Cholecystectomymentioning
confidence: 99%
“…Socioeconomic disparities in outcomes after cholecystectomies exist, and uninsured patients and minorities have been shown to be more likely to undergo emergency surgery. 8 Barriers to health-care access in these populations may subsequently increase LOS, costs, and complications. Younger patients at CHs may have longer LOS because of issues with postoperative pain tolerance, slower recovery times, or more conservative healthcare team members.…”
Section: Discussionmentioning
confidence: 99%